Auditor Salary and Audit Quality in Auditor and Educator Accountant Perspective - Shodiq, Muhammd Jafar (Educational Management, 2021)
This study examines the influence of auditor salary on audit quality by involving auditor independence and auditor skepticism as intervening variables. Previous empirical studies show that auditor salary has a significant favorable influence on audit quality. However, the influence is presumed not directly as it is. The variable of auditor independence and skepticism is considered involved as an intervening variable between auditor salary and audit quality. Data of the study was obtained from auditor and educator accountant response on the question indicators from the fourth measured variables. These two perspectives are essential, considering that auditors are the result of the educational process of educator accountants. In another sense, audit quality needs to be reviewed empirically and theoretically. After examining three submitted models, it can be concluded that auditor salary influence directly and indirectly on audit quality. The indirect influence occurs through auditor independence and auditor skepticism. However, the Sobel test value shows that the indirect influence has a more significant impact than the direct influence. The Sobel test value shows the excellent mediation role of auditor independence and skepticism variables on the relation between auditor salary and audit quality.